Unlocking the Early Bronze Age: attempting to extract Umm an-Nar tombs from a remotely sensed Hafit dataset (poster) - Deadman, W.M. (Proceedings of the Seminar for Arabian Studies, 2012)
In recent research, Google Earth was used successfully to detect 2840 Early Bronze Age tombs in the Wādī ʾAndām area of al-Sharqiyyah, Oman. The distribution of these tombs in their landscape was analysed using geographic information systems (GIS) in an attempt to shed light on the nature of Hafit society: it was tentatively concluded that they were constructed by a nomadic pastoralist population, but a concern with the dataset was the possible erroneous inclusion of a significant number of Umm an-Nar tombs, which would cast doubt on the integrity of the methodology and conclusions of the investigation. In order to assess the extent of the problem, published tombs from both periods were analysed using GIS, and a simple statistical methodology was utilized to extract a subset of structures that had a 'high probability' of dating to the later period. Seventy-one tombs met these parameters, and when examined on the ground all dated to the Hafit period. This result means that the Wādī ʾAndām dataset may be used to investigate Hafit society, but further research and development of the remote sensing methodology is needed.